Studies on the Thermal properties of untreated and chemically treated Palmyra Palm Leaf Base Fibres - Thiruchitrambalam, M; Shanmugam, D; Thiru Murugan, Rama.; Venkateswaran, N (International Journal of Engineering and Technology, 2026)
Palmyra( Borassus flabefllier )palm leaf base fibre, a natural fibre extracted from palmyra palm tree was chosen and chemicals such as sodium hydroxide , benzoylchloride , and potassium permanganate for pre treatment procedures . Effect of these treatments on the thermal properties were determined experimentally.